Controlling Effect of HSABC Algorithm on the Unit Commitment of Power System Operation - NA, Arif; Hiyama, Takashi (Frontier Energy System and Power Engineering, 2021)
The total operating cost may be expressed in an Economic Power System Operation (EPSO). Technically, this fee is presented to meet total demand for load by individual generating unit costs based on the schedule of engaged energy outputs (EEO). The minimum operating cost is currently achieved by considering economic and emission dispatches, which are made up of the problem of a combined economic and emission dispatch (CEED). The latest artificial intelligent calculation, Harvest Season Artificial Bee Colony Algorithm, is used to identify EEO using the IEEE-62 bus system based on a low cost of CEED. The results of the simulation show that HSABC has short time and rapid convergences. Space areas have various impacts on the performance of HSABC Algorithm on the CEED.